What Influences the Online Purchasing of Electrical Equipment Products? - UTOMO, Priyo; SUTRISNO, Timotius F. C. W. (KnE Social Sciences, 2021)
The purpose of this research was to examine the influence of e-trust, risk perception and company reputation on purchasing decisions. This was quantitative research, using the SEM data analysis method assisted by AMOS software. Data collection was done by distributing an e-questionnaire (a google form); 270 responses were obtained. Participants were consumers who had already purchased electrical equipment online in Denpasar and Surabaya. E-trust, risk perception and company reputation significantly influenced purchasing decisions. Keywords: E-trust, risk perception, company reputation, purchase decision